Pengaruh Penggunaan Media Kartu Struktur Atom Dan Sistem Periodik Terhadap Hasil Belajar Siswa Kelas XI SMA Negeri 6 Palu - Marwah, Marwah; Sabang, Sri Mulyani; Tangkas, I Made (Universitas Tadulako, 2014)
The use of instructional media could help teachers to develop and deepen in teaching and learning process in the classroom. This study aims to determine the effect of using atomic structure card media and periodic systems toward learning outcome of the eleventh grade students of SMA Negeri 6 Palu. The population in this study was all of the eleventh grade students on Science Program of SMA Negeri 6 Palu in the academic year 2013/2014 which consists of 3 classes. The sample in this study was 30 students of Science Program 1 as the experimental class and 32 students of Science Program 2 as the control class. Testing research data used statistical analysis of the t test (right) with the prerequisite test, test for normality, and homogeneity. The data analysis result obtained for the average score in the experiment class X1 = 68.03 with deviation standard = 10.50 and the control class X2 = 54.75 with deviation standard = 9.57. Based on the testing result of hypothesis by statistical t-test values obtained right side of tcounted> ttable is 5.37 > 1.67 with a confidence level of 0.05 and degrees of freedom = 60. From the results of hypothesis testing, then, Ho was rejected so it can be concluded that there is a better influence in using atomic structure card media and periodic system toward learning outcome of the leventh grade students of SMA Negeri 6 Palu.